Proceedings of the Eighth International Conference on Engineering Computational Technology
DOI: 10.4203/ccp.100.88
|View full text |Cite
|
Sign up to set email alerts
|

A Multilevel Technique based on Nested Local Meshes for Nonlinear Mechanics

Abstract: In this paper an adaptive multilevel mesh refinement method, coupled with the Zienkiewicz and Zhu a posteriori error estimator, is applied to solids mechanics with the objective of conducting reliable nonlinear studies in acceptable computational times and memory space. The approach presented in this paper is first validated on linear behaviour, on two and three dimensional simulations. Then nonlinear behaviour is studied. Advantages and limitations of the local defect correction method in solids mechanics pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Moreover, the use of refinement ratio greater than 2 could be attractive in the sense that it could allow us to obtain the same error level with less sub-grids [13]. In [12,13], it had been shown that for a refinement ratio of 4, the mesh convergence remains in Oðd h fine Þ. That is why we decide to compare our LDC method applied on an initial mesh of size h i =2, with 1 to 7 sub-grids of refinement ratio 2 to 1 to 4 sub-grids of refinement ratio 4.…”
Section: Comparison With a Global H-adaptive Refinement Techniquementioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the use of refinement ratio greater than 2 could be attractive in the sense that it could allow us to obtain the same error level with less sub-grids [13]. In [12,13], it had been shown that for a refinement ratio of 4, the mesh convergence remains in Oðd h fine Þ. That is why we decide to compare our LDC method applied on an initial mesh of size h i =2, with 1 to 7 sub-grids of refinement ratio 2 to 1 to 4 sub-grids of refinement ratio 4.…”
Section: Comparison With a Global H-adaptive Refinement Techniquementioning
confidence: 99%
“…For more details about the own effects on the cladding of the pellet hourglass configuration, the reader is referred to [12,13].…”
Section: Verification Studymentioning
confidence: 99%
See 1 more Smart Citation
“…These initial results suggest that the LDC solver may be also efficient with more complex structural mechanics behaviour, such as nonlinear path-dependent behaviour. This method has in fact already been successfully applied to ''one-time-step'' nonlinear behaviour (see [77]) and give promising results.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%